Stückelberg-interferometry with ultra-cold atoms - Plötz, Patrick; Wimberger, Sandro (The European physical journal. D, Atomic, molecular, optical and plasma physics, 2011)
Stückelberg oscillations have been observed in recent experiments with ultra-cold atoms.We show that and how precisely ultra-cold atoms in an accelerated two-band lattice are acontrolled realization of Landau-Zener-Stückelberg interferometry. We derive simpleformulae for the time-dependent and time-averaged occupation of the energy bands andcompute interference patterns for parameters directly accessible in experiments withultra-cold atoms.
Gesehen am 23.12.2022